Service delivery in Kenyan district hospitals - what can we learn from literature on mid-level managers? - Nzinga, J; Mbaabu, L; English, M (BioMed Central, 2013)
BACKGROUND: There is a growing emphasis on the need to tackle inadequate human resources for health (HRH) as an essential part of strengthening health systems; but the focus is mostly on macro-level issues, such as training, recruitment, skill mix and distribution. Few attempts have been made to understand the capability of health workers, their motivation and other structural and organizational aspects of systems that influence workforce performance. We have examined literature on the roles of mid-level managers to help us understand how they might influence service delivery quality in Kenyan hospitals. In the Kenyan hospital settings, these are roles that head of departments who are also clinical or nursing service providers might play. METHODS: A computerized search strategy was run in Pub Med, Cochrane Library, Directory of Open Access Journals Social Science Research Network, Eldis, Google Scholar and Human Resources for Health web site databases using both free-text and MeSH terms from 1980 to 2011. In addition, citation searching from excluded and included articles was used and relevant unpublished literature systematically identified. RESULTS AND DISCUSSION: A total of 23 articles were finally included in the review from over 7000 titles and abstracts initially identified. The most widely documented roles of mid-level managers were decision-making or problem-solving, strategist or negotiator and communicator. Others included being a therapist or motivator, goal setting or articulation and mentoring or coaching. In addition to these roles, we identified important personal attributes of a good manager, which included interpersonal skills, delegation and accountability, and honesty. The majority of studies included in the review concerned the roles that mid-level managers are expected to play in times of organizational change. CONCLUSION: This review highlights the possible significance of mid-level managers in achieving delivery of high-quality services in Kenyan public hospitals and strongly suggests that approaches to strengthen this level of management will be valuable. The findings from this review should also help inform empirical studies of the roles of mid-level managers in these settings.